Annual Bluegrass (Poa annua) Biotypes Exhibit Differential Levels of Susceptibility and Biochemical Responses to Protoporphyrinogen Oxidase Inhibitors. Issue 5 (11th September 2018) - Yu, Jialin; McCullough, Patrick E.; Czarnota, Mark A.
Abstract: An annual bluegrass ( Poa annua L.) biotype with limited susceptibility to POST flumioxazin applications was identified in Georgia. The objectives of this research were to quantify tolerance levels of this biotype (R-biotype) to protoporphyrinogen oxidase (PPO) inhibitors and characterize physiological responses to flumioxazin. In dose–response experiments on 3- to 5-tiller plants, flumioxazin and sulfentrazone rates required to reduce dry-shoot biomass 50% from the nontreated were >14.5 and 10.4 times greater for the R-biotype, as compared with a susceptible (S)-biotype, respectively. Establishment of the R-biotype from seed was completely controlled by PRE applications of flumioxazin and oxadiazon, similar to the S-biotype. Tank mixtures of chlorpyrifos with flumioxazin did not enhance biomass reductions of the R-biotype, suggesting that tolerance levels may not be related to cytochrome P450–associated metabolism. In laboratory experiments, the R-biotype averaged 27% less electrolyte leakage, as compared with the S-biotype, after flumioxazin treatments. Lipid peroxidation in the R-biotype, as measured by malondialdehyde levels, averaged 25% less than the S-biotype at 72 h after broadcast flumioxazin treatments at 280 and 560 g ha −1 . The tolerance to POST applications of PPO inhibitors in this P. annua biotype is associated with less lipid peroxidation and electrolyte leakage as compared with the S-biotype. These biochemical differences in biotypes may contribute to erratic levels of POST control from flumioxazin and could contribute to PPO-inhibitor resistance.